Corporate Governance and Public Corruption - Cusolito, Ana (2012)
Corporate governance in the private sector and corruption are important for economic development and private sector development. This paper investigates how corporate governance in private-sector media companies can affect public corruption. The analytical framework, based on models of corporate governance, identifies two channels through which media ownership concentration affects corruption: an owner effect, which discourages corruption and a competition-for-control effect that enhances it. When the ownership structure of a newspaper has a majority shareholder, the first effect dominates and corruption decreases as ownership becomes more concentrated in the hands of majority shareholders. Without majority shareholders, the competition-for-control effect dominates and corruption increases with the concentration of ownership of the media company. Thus, the paper shows that cases of intermediate media-ownership concentration are the worst at promoting public accountability, while extreme situations, where the ownership is completely concentrated or widely held, can result in similar and lower levels of corruption.